Bank profitability and economic growth - Paul-Olivier Klein; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper analyses the effect of bank profitability on economic growth. While policymakers have shown major concerns for low levels of bank profitability, there are no empirical studies on the growth effects of bank profitability. To fill this gap, we investigate the impact of bank profitability on economic growth using a sample of 133 countries during the period 1999–2013 with several empirical approaches. Our first major conclusion is that a high current level of bank profitability contributes positively to economic growth. Our second conclusion is that the past level of bank profitability exerts a negative influence on economic growth leading to the absence of significance for the overall bank profitability. Hence, the positive impact of bank profitability on economic growth is short-lived. These findings are robust to a battery of robustness checks, including those using alternative measures for profitability and growth.
URN:NBN:fi:bof-201807031683
Keywords: G21; O16; O40; 330